Evaluation Of Company Compliance With Consumer Protection Standards - Rahmat Rahmat (PT. Anagata Sembagi Education, 2024)
Consumer protection is an important aspect in creating a healthy relationship between businesses and consumers. With clear regulations in place, consumer rights can be protected from potential risks and unethical business practices. This study aims to evaluate companies' compliance with consumer protection standards with a focus on existing regulations. Consumer protection is an important effort in safeguarding consumer rights and increasing public trust in companies. The research method used is normative juridical research, which examines the application of positive legal principles related to consumer protection, including an analysis of Law Number 8 Year 1999. The results show that many companies still experience non-compliance due to internal and external factors, such as unclear regulations and weak supervision. Companies' non-compliance with consumer protection standards is caused by internal factors, such as corporate culture that does not support business ethics, and external factors, such as weak law enforcement. To improve compliance, companies need to develop clear internal policies, conduct regular employee training, and implement stricter monitoring and evaluation. Comprehensive education and the use of supporting technology are also important to ensure that consumer protection is a top priority for companies.